Fan Economy and Purchasing Decisions: The Role of Product Diversity, Price Perception, and Promotion in the K-Pop Merchandise Market in Indonesia - Vini Reski Utami; Winda Cantika Rispo; Juwitan Intan (Journal of Economics Business Industry, 2024)
The development of the Korean Wave (Hallyu) in Indonesia has significantly driven the growth of the K-pop merchandise market. This study aims to analyze the influence of product diversity, price perception, and promotion on purchasing decisions for K-pop merchandise. A quantitative research method with a survey approach was employed, using questionnaires distributed via WhatsApp and Instagram social media platforms. The research sample consisted of 97 respondents selected through purposive sampling, with the criterion that participants had shopped at the Cherrys.lab store more than once. Data analysis was conducted using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method with SmartPLS software. The results indicate that product diversity has a significant effect on purchasing decisions (T-statistic = 2.261; P-value = 0.024), price perception has a significant effect on purchasing decisions (T-statistic = 3.637; P-value = 0.000), and promotion has a significant effect on purchasing decisions (T-statistic = 10.710; P-value = 0.000). Promotion is the most dominant variable influencing purchasing decisions. The R-Square value of 0.942 indicates that 94.2% of the variance in purchasing decisions is jointly explained by the three variables. This study provides practical implications for K-pop merchandise store managers to optimize digital-based promotional strategies, expand product diversity, and establish competitive pricing in order to increase consumer purchasing decisions.